ASP.NET MVC 1.0 Website Programming : Problem - Design - Solution. - Berardi, Nick (John Wiley & Sons, 2009)
Perfectly suited to the innovative Problem Design Solution approach, ASP.NET MVC is a new development model that separates code for the data, look, and business processes of a Web site. This nuts-and-bolts guide thoroughly covers creating a Web site with MVC and discusses solving the most common problems that you may encounter when creating your first application or trying to upgrade a current application. The material is based on the highly praised and widely used TheBeerHouse ASP.NET Starter Kit that was developed in the bestselling ASP.NET 2.0 Website Programming: ProblemÂ?DesignÂ?Solution.